Oral Hygiene and Pocket Depth among Acute Myeloid Leukemic Adult Patients in Erbil City - Mohammed Hussein , Vian; Rassul Hussein, Shahida (Diyala Journal of Medicine, 2022)
Background:Leukemia is a hematological disease with oral manifestations. Objective: To assess gingival health and periodontal pocket depth of different age groups of both genders. Patients and Methods: A total of 74 patients (aged 20-70 years) who were diagnosed with Acute Myeloid Leukemia (AML) were examined and compared with 74 control group. The oral hygiene status, gingivitis and periodontal pocket were examined. Dental plaque was detected by means of the Silness J & Löe 1, gingival index by Löe H & Silness 2 and calculus index by Ramfjord 3. While the pocket depth was measured by using Williams probe 4. Results: Demonstrated that ; the total mean for plaque(1.31) ,gingival (1.23) , calculus(0.30) scores and pocket depth (2.95) for control group while the total mean of plaque(1.75) ,gingival (1.57) , calculus(0.45) scores and pocket depth (3.22) for leukemic group with significant differences fore plaque (P-value =0.000) and gingival(P-value =0.004) score but with no significant difference for calculus score(P-value =0.095)and pocket depth (P-value). =0.103)between both groups . A larger number and percentage of male suffered from this disorder than female and a higher number and percentage of AML were aged between (20-29) years. Conclusion: AML patients in the present study showed more dental plaque, more gingivitis, more calculus score and more pocket depth, compared with healthy patients.